2015
DOI: 10.1007/s00138-015-0659-0
|View full text |Cite
|
Sign up to set email alerts
|

Forest species recognition based on dynamic classifier selection and dissimilarity feature vector representation

Abstract: Multiple classifiers on the dissimilarity space are proposed to address the problem of forest species recognition from microscopic images. To that end, classical texturebased features such as Gabor filters, local binary patterns (LBP) and local phase quantization (LPQ), as well as two keypoint-based features, the scale-invariant feature transform (SIFT) and the speeded up robust features (SURF), are used to generate a pool of diverse classifiers on the dissimilarity space. A comprehensive set of experiments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
22
0
2
Order By: Relevance
“…The Dichotomy Transformation has already been used in various contexts, such as: bird species identification Zottesso et al (2018), forest species recognition Martins et al (2015), writer identification Bertolini et al (2016) and also for handwritten signature verification Rivard et al (2013); Eskander et al (2013); Souza et al (2018b).…”
Section: Wi Dichotomy Transformation For Handling Hsv Data Difficultiesmentioning
confidence: 99%
“…The Dichotomy Transformation has already been used in various contexts, such as: bird species identification Zottesso et al (2018), forest species recognition Martins et al (2015), writer identification Bertolini et al (2016) and also for handwritten signature verification Rivard et al (2013); Eskander et al (2013); Souza et al (2018b).…”
Section: Wi Dichotomy Transformation For Handling Hsv Data Difficultiesmentioning
confidence: 99%
“…As a method for the extraction of image information, which is one of the important processes in image recognition, a texture analysis has been utilized in a variety of fields such as remote sensing and medical imaging. Several authors have also reported attempts of the application of these techniques to wood identification [7][8][9][10][11][12][13][14][15][16][17][18][19], which are particularly active in tropical areas. Tropical timber is an important biological and economical resource in the developing world; thus, wood identification is demanded at trading locations to circulate proper wood in the market as well as to keep illegally logged timber under observation.…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, an automated wood identification system is highly demanded because the development of human resources is important, but it is not straightforward to train people to have in-depth anatomical knowledge and experience to cover the large diversity of tropical hardwood species. Many studies have mostly used optical micrographs [10,11,14,19] or stereograms [7-9, 12, 13, 15-18], whose resolution was a several micrometers at worst. Under such conditions, the arrangements of vessels and axial parenchyma were clearly recorded and used as image information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many studies of wood image recognition have been conducted in the last decade [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], which mainly focused on protecting tropical timber in trading locations.…”
mentioning
confidence: 99%